Penerapan Strategi dan Teknologi PHT untuk Mendukung Syarat Kualitas Produk Pertanian dalam Menghadapi Era Perdagangan Global (Review) - GEDE MENAKA ADNYANA; I PUTU DHARMA; UTAMI UTAMI (Fakultas Pertanian Universitas Udayana, 2016)
Implementation Strategy and Technology of IPC to Support Terms of Quality Agricultural Products Era Dealing in Global Trade. In the era of free trade in the world, export-import activities, especially agricultural products and other dairy products, according to the agency authorized trade-WTO states that the flow of goods can no longer inhibited by rules such as tariffs and other barriers, but by the quality standards of agricultural and processed products. Faced with this situation, the government of Indonesia through the Ministry of Agriculture has issued regulation No. 27/Permentan/PP.340/5/2009 about oversight of expenditures and revenues fresh food of plant origin. In addition, it was also applied to the field school IPC and implement SOPs for agricultural products exported as coffee and cocoa.